Piper ornatum for wound cleansing in diabetic foot ulcers - Pravita Sari, Pricilia; Margono, Margono; Wahyuningtyas, Eka Sakti (Universitas Muhammadiyah Magelang, 2023)
Macroangiopathy leads to diabetic ulcers due to vascular insufficiency and neuropathy. Treating such wounds requires innovative approaches, including wound washing with a decoction of red betel leaves (Piper ornatum). This case study aims to evaluate the effectiveness of this method in patients with diabetic foot ulcers. The study employs a descriptive design with purposive sampling. The participant, Mrs. S, is a 41-year-old woman with grade 1 diabetic foot ulcers. Data were collected through participatory observation, unstructured interviews, and documentation. Results indicated that wound cleansing with red betel leaf decoction improved wound tissue regeneration. The Bates Jensen Wound Assessment Tool score decreased from 35 to 28 after four treatments, indicating significant wound regeneration. It is hoped that healthcare professionals will adopt this method to optimize wound healing. Keywords: Wound cleansing agent; innovation; clinical practice; diabetic foot ulcers; healthcare professionals